Exploring the link between visceral fat and cardiovascular disease in type 2 diabetes: evidence from ct measurements - Wu, Qing-Wu; He, Yu-Hua; Li, Pei-Heng; Gu, Shi-Li; Song, Ran; Zhang, Dong-Ying; Zhu, Yun-Feng (Frontiers in Endocrinology, 2025)
BackgroundVisceral fat is a well-established risk factor for cardiovascular disease (CVD) in patients with type 2 diabetes (T2DM). While visceral fat is recognized as a risk factor for CVD in T2DM patients, precise quantification of this relationship using direct CT measurements requires further validation in large populations. This study seeks to examine the cross-sectional association between VFA, as measured by CT, and prevalent CVD in T2DM patients, with the aim of informing risk management strategies in this group.MethodsThis cross-sectional study analyzed data from 3,173 T2DM patients who underwent health screenings at Xinxiang First Affiliated Hospital between January 2020 and January 2025. CVD was defined as self-reported physician-diagnosed coronary artery disease, angina pectoris, stroke, congestive heart failure, or myocardial infarction, with verification through follow-up interviews when needed. CVD served as the dependent variable, while VFA, measured by CT, was the independent variable. VFA was categorized into quartiles. The association between VFA and CVD was assessed using univariate and multivariate analyses, smooth curve fitting with generalized additive models, and subgroup analyses.ResultsThe prevalence of CVD increased progressively across VFA quartiles in T2DM patients. After adjusting for confounders, VFA remained independently associated with prevalent CVD (OR = 1.43, 95% CI: 1.12 – 1.65, P < 0.001). Patients in the highest VFA quartile (Q4) had a 2.04-fold higher liver fat content compared to those in the lowest quartile (Q1) (95% CI: 1.56 – 2.94, P < 0.001). Subgroup analyses confirmed that this association was consistent across different populations (interaction P > 0.05).ConclusionVFA is independently associated with prevalent CVD in T2DM patients. Future research should focus on the link between abdominal fat accumulation and CVD in this population.